Analysis of the Implementation of DevSecOps Policies and Technology towards Reducing the Number of Vulnerabilities in the Telecommunications Industry: Case Study of MyApps Application at PT XYZ - Prayogo, Dimas; Ramli, Kalamullah (Jurnal Locus Penelitian dan Pengabdian, 2025)
The acceleration of digitalization is highly needed by the telecommunications industry to compete in both national and international markets. To meet this challenge, the telecommunications industry has begun to implement a new approach in application development and deployment, namely by utilizing cloud computing and agile methods. In this case, PT XYZ applies the DevSecOps approach so that each development cycle includes aspects of development speed, security, and operations in an integrated manner. However, in the early stages of implementing the DevSecOps policy, various vulnerabilities were found in the application being developed, in this case the MyApps application. This problem shows that a technology or early detection mechanism is needed to identify vulnerabilities before the application enters the production stage. Therefore, this study was conducted with the aim of reducing the number of vulnerabilities in the MyApps application, thereby enabling safer and more efficient application development. The results of the study showed a reduction in the number of vulnerabilities from SAST by 78.1%, from container scans by 86.7%, and total vulnerabilities by 83.6% in the MyApps application, thus minimizing the risk of cyber attacks in the future.